Refuge in Abundance: Puʻuhonua o Kakaʻako and Native Hawaiian Politics of Family and Place in the Early Twentieth Century - Bourgette, Alika (My University, 2024)
“Refuge in Abundance” investigates the ways early-twentieth century Kānaka Maoli (Native Hawaiians) built and perpetuated puʻuhonua (refuge and abundance) within the shoreline neighborhood of Kakaʻako, Honolulu. Native Hawaiian lands and waters allowed early-twentieth century communities to access deep memories of interconnection important to creating the Indigenous futures. As practiced through place-based cartographic and Indigenous storytelling methods, Indigenous world-making provides alternatives to capital-driven narratives of apocalyptic decline. Through a relational mapping of Hawaiʻinuiākea (Greater Hawaiʻi) that flows as water through the skies, along the streams, and out to sea, Native Hawaiian political writers across the nineteenth century engaged in intergenerational conversations that contemplated future needs and desires during a tumultuous era of imperial upheaval and U.S. colonial occupation. Kingdom-era transformations of land tenure during the Māhele ʻĀina (Land Division) of 1848 and subsequent Kuleana Act of 1850 wrought declining fortunes for makaʻāinana (commoner) Native Hawaiians. Many makaʻāinana lost access to lands as they had for generations, despite protections and laws that incentivized their private land ownership. However, by the first decades of the twentieth century, the abundant foodscape of Indigenous Honolulu challenged the interests of settler officials in the fledgling Territory of Hawaiʻi. Relying on expanded kin and food networks from mountains to sea, Native Hawaiians braided a constellation of care and anti-eviction efforts across Honolulu. In the 1910s and 1920s, where the officials and institutions of the Territory of Hawaiʻi saw crime, filth, and racial decline, Kakaʻako community members brought together their “many hands” to create joy and usher in new life. As a form of political expression, engagement in genealogical connections to lands, waters, and skies demonstrated through midwifery, child rearing, and schoolteaching provided Hawaiian and non-Hawaiian community members alternatives to participation in colonial subjecthood as “residents” of the U.S. Territory of Hawaiʻi. As frequent targets for removal and incarceration by city police and territorial lawmakers, Native Hawaiian youths circumvented colonial organization of school and playground spaces through expanded kin and familial relationships they formed with their schoolteachers. Collective joy also reverberated through the expression of multiple Indigenous genders and sexualities by the actions of Native Hawaiian artists and entertainers who critiqued colonial capitalism in their shaping of emerging tourism. The arrival of passenger steamships in the early twentieth century presented Native Hawaiian women, men, and queer folks opportunities not only to make money, but also to carve out expansive understandings of Indigenous genders that defied limited, binary definitions and roles. As exhibited bodies, fetishized companions, and musical performers, Native Hawaiian beachboys served as living souvenirs for affluent patrons on the North American continent. Native Hawaiian boys and young men circumvented the colonial and racial organization of spaces normally reserved for haole elites in Hawai‘i and elsewhere. Through the creative joy and life-affirming worlds mutually conceived by Indigenous lands, waters, peoples, “Refuge in Abundance” celebrates the generations of Native Hawaiians who fostered the future for us, their descendants and protectors for time to come.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Environmental History; Gender Studies; Native American Indigenous Studies; Native Hawaiian; Indigenous studies; Gender studies; Environmental justice; History